(untitled) (Revista Archai, 2022)
The phrase of the English poet Samuel Taylor Coleridge, “all men are born Aristotelians or Platonists”, brought up by Borges on several occasions, is well known and quoted. But what in my opinion has not been explored so much is the sense that the disjunction implied in that phrase assumes in Borges’ work. The purpose of this paper is to analyze how this disjunction between Plato and Aristotle plays out in the light of the references Borges makes to them throughout his work. To this end, I am interested in relieving some Platonic and Aristotelian motifs used by Borges as a function of his fictional universe, in order to evaluate the meaning and scope of such disjunction. My hypothesis is that it assumes in Borges’ work a weak and inclusive sense, which positions this author in a place between Plato and Aristotle.